SIGNS, SYMPTOMS, AND MECHANISMS IN FIBROMYALGIA: AN EXPERIENCE REPORT AND REVIEW WITH A NEUROSCIENTIFIC FOCUS - da Silva Cavalcante, Marcelino; Andrade, Jaira (Health and Society, 2025)
This article presents an expanded analysis of the personal report of an individual with fibromyalgia, describing signs and symptoms such as chronic widespread pain, fatigue, sensory hypersensitivity, autonomic changes, and cognitive impairment. The report is integrated with contemporary scientific evidence on neurobiological mechanisms, including central sensitization, nociceptive dysfunction, neurotransmitter dysregulation, autonomic imbalance, and altered brain connectivity. Diagnostic challenges, psychosocial implications, and multidimensional therapeutic strategies are discussed. The text aims to contribute to the dialogue between subjective experience and scientific evidence, reinforcing the biopsychosocial complexity of fibromyalgia.